Penerapan Metode Metode Dempster Shafer Untuk Mendiagnosa Penyakit Ginjal Berbasis Web - Sri Wahyuni; Jeperson Hutahaean; Cecep Maulana (Building of Informatics, Technology and Science (BITS), 2022)
Kidney disease is one of the non-communicable diseases with the highest proportion in Indonesia and is one of the causes of death in this country. Especially in Asahan District, the number of kidney patients who die is increasing over time, so there needs to be effective treatment so that kidney disease is no longer feared by the public because it is easy to treat. Many patients who experience kidney disease are getting worse because they cannot detect the early symptoms of kidney disease, which is still considered trivial. There is no information about kidney disease and its symptoms, making it difficult to diagnose the disease. In the diagnosis of this disease is limited to conventional diagnosis with doctors. it is necessary to build a system on a computer application to help diagnose kidney disease. To determine the level of kidney disease, an expert diagnostic system was made with the method used in this case is the Dempster Shaper method. This method is an approach method that is used is to measure the strength of evidence (facts) in supporting a set of propositions by providing a way to combine evidence from sources and bring or provide a level of confidence (represented through the trust function) which takes from all available evidence with input. required attributes and the likelihood of the disease and associated symptoms. The result of the implementation of the system is that the system provides an alternative to the symptoms experienced by the patient and the results of the process the system will provide information on kidney infection by 60% and also provide solutions with treatment